2005
DOI: 10.1126/science.1110689
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clock Control by SUMOylation of BMAL1

Abstract: The molecular machinery that governs circadian rhythmicity is based on clock proteins organized in regulatory feedback loops. Although posttranslational modification of clock proteins is likely to finely control their circadian functions, only limited information is available to date. Here, we show that BMAL1, an essential transcription factor component of the clock mechanism, is SUMOylated on a highly conserved lysine residue (Lys259) in vivo. BMAL1 shows a circadian pattern of SUMOylation that parallels its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
220
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(224 citation statements)
references
References 29 publications
4
220
0
Order By: Relevance
“…A recent study revealed that constitutive high expression of BMAL1 protein in Rev-Erb␣-disrupted mice still allows robust circadian molecular and behavioral rhythms (12). Moreover, it has been shown that sumoylation of BMAL1 influences posttranscriptional features of BMAL1 and that this process is CLOCK-dependent (13). Taken together, these results suggest that posttranslational modification of BMAL1 is an important prerequisite for its performance in the circadian oscillator.…”
supporting
confidence: 56%
“…A recent study revealed that constitutive high expression of BMAL1 protein in Rev-Erb␣-disrupted mice still allows robust circadian molecular and behavioral rhythms (12). Moreover, it has been shown that sumoylation of BMAL1 influences posttranscriptional features of BMAL1 and that this process is CLOCK-dependent (13). Taken together, these results suggest that posttranslational modification of BMAL1 is an important prerequisite for its performance in the circadian oscillator.…”
supporting
confidence: 56%
“…CLOCK, BMAL1, PER, and possibly also CRY proteins are phosphoproteins in vivo (Lee et al 2001). Moreover, BMAL1 was shown to be sumoylated (Cardone et al 2005) and, very recently, acetylated (Grimaldi et al, this volume). These modifications specifically alter the properties and functionality of the corresponding proteins by changing protein stability, subcellular localization, activity, or complex formation.…”
Section: Introductionmentioning
confidence: 99%
“…Other posttranslational modifications have also been found on core clock proteins. Thus, CLOCK can be sumoylated (Cardone et al 2005) (Asher et al 2010). PER2 and BMAL1 can be acetylated (by CLOCK [Doi et al 2006;Grimaldi et al 2009] and, probably, additional acetyltransferases) and deacetylated in a circadian fashion by the NAD þ -dependent deacetylase Sirtuin 1 (SIRT1) (Asher et al 2008;Nakahata et al 2008).…”
mentioning
confidence: 99%